Partisipasi Keluarga dalam Pengelolaan Sampah Pesisir di Kecamatan Belopa Utara Kabupaten Luwu - Siti Aisa Lamane; Sarmedi Sarmedi; Adi Rianto Suprayitno (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
The problem of waste management in the coastal environment is a classic one that is difficult to overcome. Indonesia is one of the countries that contributes to the waste on the coast. The more advanced the human lifestyle, the more waste is produced. The goods consumed and used are becoming increasingly varied. Almost all of these items have packaging. There is no denying that information is circulating on social media about heaps of rubbish on the coast in almost all parts of Indonesia. This study aims to analyze community behaviour towards coastal waste management, which can influence family perceptions of coastal waste management in Lamunre Village, North Belopa District, Luwu Regency. This research was conducted in Lamunre Village, Lamunre Tengah Village, and Sabe Village. Data collection was carried out in February-March 2023. The Respondents were 100 heads of households aged 20-60 years in Lamunre Village, Lamunre Tengah Village, and Sabe Village, North Belopa District, Luwu Regency. This study used survey methods and descriptive. The data is analyzed using Partial Least Square (PLS) with the SmartPLS3 app. The results showed that the number of dependent family members, type of work, attitude towards waste management, management skills, willingness to accept service tertiary institutions, and willingness to cooperate with the local government affected participation in coastal waste management in North Belopa district, Luwu Regency.